2018
DOI: 10.1155/2018/6249085
|View full text |Cite
|
Sign up to set email alerts
|

TRIF Regulates BIC/miR-155 via the ERK Signaling Pathway to Control the ox-LDL-Induced Macrophage Inflammatory Response

Abstract: Toll/IL-1R-domain-containing adaptor-inducing IFN-β (TRIF) is an important adaptor for TLR3- and TLR4-mediated inflammatory signaling pathways. Recent studies have shown that TRIF plays a key role in vessel inflammation and atherosclerosis; however, the precise mechanisms are unclear. We investigated the mechanisms of the TRIF-regulated inflammatory response in RAW264.7 macrophages under oxidized low-density lipoprotein (ox-LDL) stimulation. Our data show that ox-LDL induces TRIF, miR-155, and BIC expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Our functional data further validated that TRAM may serve as a general membrane stress sensor for monocyte activation given that the induction of ICAM-1 and CCL5 by oxLDL is ablated in TRAM-deficient monocytes. Our data can also reconciles previous independent findings that implicate TRAM as a key signaling adaptor for oxidized phospholipid-induced monocyte activation 63,64 . Our data demonstrating the role of 4-PBA in alleviating TRAM clustering and reducing monocyte inflammatory polarization suggest that additional compounds that relieve membrane stress may be similarly effective in dampening monocyte low-grade inflammatory memory.…”
Section: Discussionsupporting
confidence: 92%
“…Our functional data further validated that TRAM may serve as a general membrane stress sensor for monocyte activation given that the induction of ICAM-1 and CCL5 by oxLDL is ablated in TRAM-deficient monocytes. Our data can also reconciles previous independent findings that implicate TRAM as a key signaling adaptor for oxidized phospholipid-induced monocyte activation 63,64 . Our data demonstrating the role of 4-PBA in alleviating TRAM clustering and reducing monocyte inflammatory polarization suggest that additional compounds that relieve membrane stress may be similarly effective in dampening monocyte low-grade inflammatory memory.…”
Section: Discussionsupporting
confidence: 92%
“…17 Over time, the effects of host miRNAs on the life cycle of the virus have gradually been elucidated. [18][19][20] Recently, miR-155 has received significant attention because it is abundantly expressed in activated lymphocytes 21 and macrophages 22 and has been characterized as an important factor regulating T helper cell differentiation, 23 the macrophage response, 24 and pro-inflammatory transcription programs, and modulating microglia-mediated innate immune responses. 25,26 In addition, miR-155 is a TNFα-inducible microRNA predicted to bind to BACH1 mRNA, which mediates the effect of TNFα on endothelial HO-1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Moreover, ox-LDL has been confirmed to induce macrophage inflammatory response via activating ERK pathway. 32 Takemura et al 33 also suggested that ox-LDL exposure led to ERK1/2 activation in cultured human endothelial cells. Based on these previous findings, we speculate that the ERK pathway might be involved in ox-LDL-induced GA fragmentation.…”
Section: Discussionmentioning
confidence: 97%
“…Cdk1/cyclinB1 during mitosis causes the activation of ERK and subsequent phosphorylation of GRASP65 at Ser277 . Moreover, ox‐LDL has been confirmed to induce macrophage inflammatory response via activating ERK pathway . Takemura et al also suggested that ox‐LDL exposure led to ERK1/2 activation in cultured human endothelial cells.…”
Section: Discussionmentioning
confidence: 99%